2014
DOI: 10.1016/j.reprotox.2014.07.074
|View full text |Cite
|
Sign up to set email alerts
|

PVP formulated fullerene (C60) increases Rho-kinase dependent vascular tissue contractility in pregnant Sprague Dawley rats

Abstract: Pregnancy is a unique physiological state, in which C60 fullerene is reported to be distributed in both maternal and fetal tissues. Tissue distribution of C60 differs between pregnant and non-pregnant states, presumably due to functional changes in vasculature during pregnancy. We hypothesized that, polyvinylpyrorrolidone (PVP) formulated C60 (C60/PVP) increases vascular tissue contractility during pregnancy by increasing Rho-kinase activity. C60/PVP was administered intravenously to pregnant and non-pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
6
16
1
Order By: Relevance
“…Interestingly, we found that IT exposure to AgNP resulted in a depressed serotonin constrictor stress response. This finding contrasts other reports of IT exposure to various nanomaterials associated with augmented vascular constrictor responses [18,42,43] and elevated mean arterial pressure [10]. We observed that IT instillation of citrate may also have vasoactive properties as stress generation to 5-HT was further reduced compared to coronary artery segment responses from naïve or AgNP instilled rats.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that IT exposure to AgNP resulted in a depressed serotonin constrictor stress response. This finding contrasts other reports of IT exposure to various nanomaterials associated with augmented vascular constrictor responses [18,42,43] and elevated mean arterial pressure [10]. We observed that IT instillation of citrate may also have vasoactive properties as stress generation to 5-HT was further reduced compared to coronary artery segment responses from naïve or AgNP instilled rats.…”
Section: Discussioncontrasting
confidence: 99%
“…The role of the capping agents used to disperse nanomaterials has been subject of great interest and there is strong evidence that capping agent can impact a toxicity of the material on various cells types [38,44] raising the question would IT instillation of AgNP in a different vehicle result in a greater stress generation to 5-HT if not for the presence of a vehicle effect? We did observe a depressed maximal relaxation to the endothelial dependent relaxation agent acetylcholine corroborating the reports of impaired endothelial relaxation following other particle exposures [42,43]. In aggregate our results appear to reflect a poor vaso-reactivity of the coronary vascular segments but does not indicate an enhanced vaso-constrictive state of the coronary vasculature during reperfusion after ischemia that would contribute to the infract expansion.…”
Section: Discussionsupporting
confidence: 91%
“…administration of C 60 formulated in 5% PVP-saline in pregnant Sprague Dawley dams at 24 hours post exposure caused increases in vascular tissue contractility by increasing stress generation in uterine artery, thoracic aorta and umbilical vein (Vidanapathirana, et al 2014a). Real-Time PCR of aortic tissue homogenate showed a trend in increase of mRNA expression, but we found an increase in RhoA, ROCK2 and endothelial nitric oxide synthase (eNOS) protein expression in rat aortic endothelial cells at 12 hours exposure to C 60 in vitro (Vidanapathirana, et al 2014a). Based on these findings we explored the possible metabolic perturbations in the pathways involved with RhoA, RhoA-Rho kinase (ROCK), and eNOS.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the biological impacts and responses to C 60 exposure have been limited and, in some cases, contradictory. Only a few have focused on the reproductive biology and potential translocation from mother to offspring (Sumner, et al 2010a, Tsuchiya, et al 1996, Vidanapathirana, et al 2014a). A basic understanding of the distribution of C 60 during pregnancy and maternal transfer is needed to assess its safety and potential health impact on early development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation